IMPLEMENTASI E-SERVICE DALAM PENYELENGGARAAN PELAYANAN PERIZINAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KENDAL - Luwihidayanto Jati Subiyantoro; Sulistyowati . (Journal of Politic and Government Studies, 2020)
Electronic Government is the use of information and communicationtechnology that is applied and developed by the government to provide services to thecommunity. The purpose of Electronic Government is to increase the effectiveness, efficiencyand quality of government services by utilizing technology. The purpose of this study is toillustrate how the application of E-Service in an effort to improve effectively and efficientlyand to identify the driving and inhibiting factors for the implementation of E-Service in theInvestment and Integrated Services Office of One Door Kendal RegencyThe research method used uses the type of qualitative methods with a datatriangulation approach that is observation, interviews and written or archived data. Informantsin this study were the Head of Licensing and Non-Licensing Services Section and the Head ofData and Information System of the One Stop Kendal Regency Investment and IntegratedServices Office and the applicants who performed licensing services.The results showed that the electronic-based licensing service at the Office ofInvestment and Integrated Services One Door Kendal Regency is still classified in theIntegration stage. Where the Department of Investment and Integrated Services One DoorKendal Regency has used a variety of digitizing services to support services, but this has notbeen done optimally. There are 4 out of 5 types of transformation points that have not yetbeen fulfilled, including service to the community towards service by the community,traditional society towards online society, digital divide towards digital democracy anddocument-based manuals towards online governance. There are 3 factors that hinder theimplementation of E-Service in the Office of Investment and Integrated Services One DoorKendal Regency including bureaucratic structure, resources and disposition. While thedriving factor is the communication that is owned.Keywords: Electronic Government, Department of Investment and One-Stop IntegratedServices in Kendal Regency